A música no estágio supervisionado da Pedagogia: uma pesquisa com estagiárias da UFSM - Werle, Kelly (2010)
The current dissertation is articulated to the research line Educação e Artes (LP4) from Programa de Pós-Graduação em Educação, from Universidade Federal de Santa Maria (PPGE/UFSM) and the study group Formação, Ação e Pesquisa em Educação Musical (FAPEM). As general aim, it sought to comprehend how the pre-service teachers from Pedagogy course/UFSM improve the music in the teaching construction process. Specifically, it sought to know the pre-service teachers conceptions on music in and for the supervising training; to discuss about the music in the pedagogic practice carried out by the pre-service teachers; and to reflect on the music into the set of knowledge that supports the teaching of the pre-service teachers. The research has a participant nature, and was developed through a workgroup composed by four pre-service teachers from Pedagogy course/UFSM. As methodological instruments for information collect, it was used semi-structured interviews; participant observation at schools; recording book of the group meetings and of the observations at schools; participants recording book; and collective conversation. The pieces of information gotten in the research were analyzed based on the subject analysis, and the results organized into categories which ran through the multiple methodological instruments. The first part of literature review deals with the pedagogy course as a place of academic-professional education of kindergarten and initial years teachers, pointing out and discussing the supervising training as a relevant moment of this education. The second part refers to the musical and pedagogic-musical education of kindergarten and initial years teachers, detaching the musical formation in the Pedagogy course/UFSM. As results, were enhanced the relevance of musical experiences lived throughout the participants life and of the workgroup with formative device that contributed to musical construction and accomplishment in the teaching of pre-service teachers from Pedagogy.